INDONESIAN REGIONAL HIGH SCHOOL ENGLISH TEACHER USE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN POST PANDEMIC LEARNING - Indra Susanto; Adrianus Nabung (Universitas PGRI Sumatera Barat, 2025)
The integration of technology in English language teaching has been a significant development, further accelerated by the COVID-19 pandemic. Prior to the pandemic, technology was steadily being integrated into classrooms in developed countries, utilizing tools like interactive whiteboards and educational software. Additionally, digital language learning tools provided learners with flexible resources to enhance their language skills outside the classroom. However, in developing countries, including Indonesia, access to technology remained limited due to infrastructure and socioeconomic challenges, particularly in regional areas. This study looks closely at two high school English teachers’ teaching experience after the pandemic. The COVID-19 pandemic has significantly changed the way English is taught in Indonesia, especially in rural areas like Flores Island. The move to online learning sped up the use of technology in education, changing traditional teaching methods. Teachers like Elsa and Anna showed flexibility by using tools like Google Classroom for remote teaching and to increase student participation. It was also found that there is a doubt that the use of ICT in English language teaching brings a high level of dependency on the technology to the students.